NASIONALISME DI TAPAL BATAS BIRU TANTANGAN DAN PERAN MASYARAKAT PESISIR SEBAGAI PENJAGA KEDAULATAN - Nisa, Ayu; Hamka, Novita Sari; Asmawati; Deswita; Lestari, Desi; Nursuhaela; Maharani, Keyza Devina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
As the world's largest archipelagic nation, Indonesia has vast maritime territory and shares direct borders with various countries. This makes coastal areas and maritime borders strategic for maintaining national sovereignty. Coastal communities not only play a role in the maritime economy but also serve as the vanguard in monitoring and protecting Indonesian territorial waters. However, various challenges such as poor development, limited access to public services, illegal fishing activities, cross-border smuggling, and the socio-cultural influences of neighboring countries can influence the level of nationalism in coastal communities. This research uses a literature review method by analyzing various relevant scientific articles, books, and policy documents. The results indicate that coastal communities make a significant contribution to maintaining national sustainability through social oversight, reporting illegal activities, preserving maritime culture, and managing sustainable marine resources. Therefore, synergy between the government, security forces, and communities is needed to strengthen coastal development to improve community welfare while strengthening maritime nationalism.